Long‐term efficacy and tolerability of mycophenolate mofetil therapy in diffuse scleroderma skin disease. (24th March 2017) - Boulos, Daniel; Ngian, Gene‐Siew; Rajadurai, Anton; Elford, Kathleen; Stevens, Wendy; Proudman, Susanna; Owen, Claire; Roddy, Janet; Nikpour, Mandana; Youssef, Peter; Hill, Catherine; Sahhar, Joanne
Abstract: Objectives: To assess the long‐term efficacy and tolerability of mycophenolate mofetil (MMF) in patients with diffuse cutaneous systemic sclerosis (dcSSc). Methods: Patients enrolled in the Australian Scleroderma Cohort study with dcSSc and baseline modified Rodnan skin score (mRSS) ≥ 12 who were treated for a minimum of 12 months with MMF for the primary indication of skin disease were included and their prospectively collected data retrieved. Change in mRSS, the proportion with a clinically significant improvement (reduction in mRSS ≥ 5 from baseline) and adverse effects due to therapy were determined. Results: Seventy‐four participants treated with MMF were identified and of these, 42 met inclusion criteria. The mean age was 53 ± 12 years, with mean disease duration at MMF commencement of 4.8 ± 4.3 years. Twenty‐one participants (50%) commenced MMF within 2 years of disease onset and the mean duration of therapy was 2.7 ± 1.7 years. The mean mRSS at baseline was 25.9 ± 9.2 with a reduction of 3.7 ± 7.1 ( P = 0.07) after 1 year of therapy, 7.6 ± 8.3 after 2 years ( P = 0.01) and 10.5 ± 10.3 after 5 years ( P < 0.01). Response to treatment was not affected by disease duration at MMF commencement or baseline skin score. Eighteen participants (43%) demonstrated clinically significant improvement after 1 year, increasing to 92% after 4 years. Two participants (5%) ceased MMF due to adverse effects. Conclusion: MMF was associated with a modest improvement in mRSS and was well tolerated in the treatment of dcSSc. Given the natural history of dcSSc where skin involvement can spontaneously improve, randomized, placebo‐controlled studies are required to confirm whether improvement can be attributed to MMF therapy.